THE CHALLENGES OF SECONDARY LEVEL BUSINESS EDUCATION IN BANGLADESH - MD. Meraz Ahmed; Harshita Aini Haroon; Fatimah Tambi; MD. Kamal Hossain (Jurnal Pendidikan, 2021)
This paper discusses challenges of secondary level business education in Bangladesh. In particular, it explores the challenges related to curriculum, pedagogy, infrastructure and assessment systems in school. We looked at the existing facilities in schools that teach business education, teaching strategies used in the classrooms as well as the perceptions of teachers and students towards business education.Using an online survey, data was collected from 101 respondents who are secondary level school teachers. Findings reveal that challenges are mainly related to curriculum, pedagogy, infrastructure, and assessment system. However, infrastructure and students’ attitude-related challenges are the greatest challenges. In addition, we find that most of the business studies classes are attended by more than 40 students, contributing to issues related to pedagogy, infrastructure and assessment. The study recommends that the present curriculum, infrastructure, and assessment procedure of business education at the secondary level need to be upgraded for effective secondary level business education in the country. Artikel ini membahas tantangan pendidikan bisnis tingkat menengah di Bangladesh. terkait dengan kurikulum, pedagogi, infrastruktur dan sistem penilaian di sekolah, khususnya dalam hal fasilitas sekolah untuk pendidikan bisnis, strategi pengajaran yang digunakan, serta persepsi guru dan siswa terhadap pendidikan bisnis. Metode yang digunakan survei online dari 101 guru sekolah menengah. Temuan mengungkapkan bahwa tantangan terutama terkait dengan kurikulum, pedagogi, infrastruktur, dan sistem penilaian. Namun, infrastruktur dan sikap siswa merupakan tantangan terbesar. Selain itu, jumlah siswa yang cukup besar, lebih dari 40 siswa, berkontribusi pada masalah yang berkaitan dengan pedagogi, infrastruktur, dan penilaian. Studi ini merekomendasikan bahwa kurikulum, infrastruktur, dan prosedur penilaian pendidikan bisnis di tingkat menengah perlu ditingkatkan efektivitasnya di negara tersebut.